2021
DOI: 10.3390/plants10112477
|View full text |Cite
|
Sign up to set email alerts
|

Positive Salt Tolerance Modulation via Vermicompost Regulation of SOS1 Gene Expression and Antioxidant Homeostasis in Viciafaba Plant

Abstract: Strategic implementation of vermicompost as safe biofertilizer besides defensing saline soils offer dual function solving problems in developing countries. The current study aims to utilize vermicompost (VC) for amelioration of 200mM NaCl in Vicia faba Aspani cultivar and investigate the molecular role of salt overly sensitive pathway (SOS1). The experiment was conducted following a completely randomized design with three replicates. Treatments include 0; 2.5; 5; 10; 15% dried VC intermingled with soil mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Number and extent of starch grains in chloroplast of salt-stressed broad bean leaves were diminished; it may be due to the decrease in water uptake and inhibition of photosynthesis process (El Dakak et al 2021). Inhibition of photosynthetic CO 2 fixation by salinity factor may be also related to decrease in Rubisco content and activity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Number and extent of starch grains in chloroplast of salt-stressed broad bean leaves were diminished; it may be due to the decrease in water uptake and inhibition of photosynthesis process (El Dakak et al 2021). Inhibition of photosynthetic CO 2 fixation by salinity factor may be also related to decrease in Rubisco content and activity.…”
Section: Discussionmentioning
confidence: 95%
“…Shilev (2020) reported that Bacillus subtilis and Azotobacter chrooccocum stimulate plant growth in rice, maize, barely, wheat, soybean, and sunflower tolerance to NaCl stress. These microorganisms are also known to inhabit vermicompost supplemented soil and gut of Eisenia foetida earthworm that found to be benefit for the soil structure and the yield of crop plants (Satpathy et al 2020); This highlights the role of 10% VC cooperated with microorganisms in attenuating the deleterious effect of 200 mM NaCl stress on Vicia faba growth, development, and metabolism (El-Dakak et al 2021).…”
Section: Introductionmentioning
confidence: 97%
“…The significant increase of the selected bioinoculum to K + , K + /Na + and Ca 2+ revealed that this association collaborated to expel Na + ions. This might be concluded from the perspective mechanism illustrated by El-Dakak et al [ 37 ] involving salt overly sensitive signaling pathway (SOS). Thus, the proposed regulatory mechanism to control salinity stress in eggplant involves the mitigating effect of PGPR and RF through decreasing Na + and increasing K + as both share a common pump.…”
Section: Discussionmentioning
confidence: 96%
“…In the case that the compost was added along with the biochar, the positive effect became even more impressive. However, it was very evident that the type of compost had to be carefully selected, considering the requirements of the tested plant species and the composition (eventual contaminations and mineral content) of the soil [116,117]. The same observation holds true with respect to different types of biochar.…”
Section: Improving Soil Quality By the Addition Of Biocharmentioning
confidence: 98%
“…Plant performance can be improved under adverse environmental conditions by the addition of soil amendments, such as biochar. The beneficial effect of biochar on soil quality has been tested using experimental plants as different as solanaceae (tobacco) [116], fabaceae (beans) [117], and poaceae (phragmites) [118]. Stimulation of plant biomass production by the addition of biochar was most significant when using marginal soil as a matrix.…”
Section: Improving Soil Quality By the Addition Of Biocharmentioning
confidence: 99%